La sessió inaugural de la Societat Catalana d'Estudis Litúrgics en els papers de Jordi Rubió - Gudayol Torelló, Anna (Miscel·lània litúrgica catalana, 2020)
On the occasion of the 50th anniversary of the Catalan Society for Liturgical Studies (Societat Catalana d'Estudis Litúrgics), we have published and briefly commented on the documents in the Jordi Rubió i Balaguer archive on the Society's founding and its admission into the Institute of Catalan Studies in 1970, including a list of the Society's founding members.